PERSEPSI PESERTA PANDEMIC INCUBATION PROGRAM TERHADAP KEBERLANJUTAN UMKM DI KOTA DENPASAR - Rusadi, Ni Wayan Purnami; Irmayani, Ni Wayan Dian; Setiawan, I Gede Bagus Dera (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022, 2022)
The high number of workers who were economically affected by the Pandemic in Denpasar City prompted the Denpasar City Government through the Denpasar City Tourism Office to hold a Pandemic Incubation Program. The purpose of this study was to determine the effect of the Participants' Perceptions of the Pandemic Incubation Program on the Sustainability of MSEs in Denpasar City. The method used in this research is quantitative descriptive analysis, using the SEM-PLS analysis method. The sample in this study amounted to 105 participants who were selected purposively with the criteria of participants who took the PIP from start to finish for two months. PIP participants' perceptions and participants' perceptions of the sustainability of micro, small and medium enterprises in Denpasar City are in the good category. The results of the analysis also show that PIP has a positive and significant relationship to the continuation of micro, small and medium enterprises in Denpasar City.